2007
DOI: 10.1159/000095204
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Ring of the Hypostome in Hydra: Is It an Origin of the Central Nervous System of Bilaterian Animals?

Abstract: A hypothesis, ‘the nerve ring in hydra shares a common origin with the central nervous system in bilaterian animals’, is discussed in this review. The nerve ring of hydra is a ring of neurons whose neurites make a bundle running circumferentially around the hypostome just above the tentacle zone. This nervous structure has unique features in the hydra nervous system. It shows a tight association of neurons in contrast to the diffuse nerve net seen in other regions. It shows static developmental characters in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 63 publications
3
36
0
Order By: Relevance
“…Current knowledge indicates that in Hydra species the nerve net is not diffused homogenously throughout the body, but shows a far greater structural and functional complexity (Koizumi, 2007). An immunocytochemical study performed with anti-RFamide antibodies (Koizumi et al, 1992) demonstrated the occurrence of a nerve ring at the base of the hypostome in Hydra oligactis, formed by neurites of ganglion cells running circumferentially in a bundle, providing the first anatomical evidence of the existence of a ring structure previously inferred by electrophysiological studies (Kass-Simon, 1972).…”
Section: The Nervous Net Of Hydra: Anatomy Ultrastructure and Physiomentioning
confidence: 99%
See 1 more Smart Citation
“…Current knowledge indicates that in Hydra species the nerve net is not diffused homogenously throughout the body, but shows a far greater structural and functional complexity (Koizumi, 2007). An immunocytochemical study performed with anti-RFamide antibodies (Koizumi et al, 1992) demonstrated the occurrence of a nerve ring at the base of the hypostome in Hydra oligactis, formed by neurites of ganglion cells running circumferentially in a bundle, providing the first anatomical evidence of the existence of a ring structure previously inferred by electrophysiological studies (Kass-Simon, 1972).…”
Section: The Nervous Net Of Hydra: Anatomy Ultrastructure and Physiomentioning
confidence: 99%
“…An immunocytochemical study performed with anti-RFamide antibodies (Koizumi et al, 1992) demonstrated the occurrence of a nerve ring at the base of the hypostome in Hydra oligactis, formed by neurites of ganglion cells running circumferentially in a bundle, providing the first anatomical evidence of the existence of a ring structure previously inferred by electrophysiological studies (Kass-Simon, 1972). Labeling with different monoclonal antibodies or antibodies raised against different Hydra neuropeptides identified distinct subsets of neurons with specific regional distributions, dependent on axial position (Koizumi andBode, 1986, 1991;Koizumi et al, 2004). A remarkable feature of the net is, in fact, its plasticity: neurons are continually migrating to be eliminated at the apical and basal ends of the polyp together with the adjacent epithelia (Dunne et al, 1985;Bode et al, 1986), thus implying that extensive synapse remodeling must occur in physiological conditions.…”
Section: The Nervous Net Of Hydra: Anatomy Ultrastructure and Physiomentioning
confidence: 99%
“…As a consequence, the pace and timeframe of crucial evolutionary processes and novelties, like the emergence of numerous orphan genes specific for Hydra or some of its species (Khalturin et al, 2008(Khalturin et al, , 2009, cannot be assessed. Thus, as Hydra species differ in morphology, development, physiology, and ecology (Campbell, 1983;Hemmrich et al, 2007;Koizumi, 2007), the lack of a solid species level taxonomy hampers research on species specific differences in gene expression and development (Khalturin et al, 2008;Thomsen and Bosch, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[9]. In addition, certain cnidarians have centralized nerve structures, the nerve rings, which is present in anthozoans [10], [11] and medusozoans [11]–[14] including hydrozoans [15].…”
Section: Introductionmentioning
confidence: 99%